The geography of the great rebalancing in euro area bond markets during the sovereign debt crisis - Roland Beck; Georgios Georgiadis; Johannes Gräb (European Central Bank (ECB), 2015)
During the sovereign debt crisis investors rebalanced out of stressed and into non-stressed euro area countries, thereby contributing to the tensions in euro area financial markets. This paper examines the geographical pattern of this great rebalancing. Specifically, we test whether euro area and non-euro area investors adjusted their holdings of debt securities of euro area stressed and non-stressed countries dis-proportionately relative to benchmarks derived from a standard gravity model for portfolio choice. We find that non-euro area investors under-invested in stressed euro area countries, but did not over-invest in non-stressed euro area countries. As regards intra-euro area flows, we do not find evidence for a disproportionate slowdown of capital flows from non-stressed into stressed euro area countries. Instead, our results suggest that investors in stressed euro area countries disproportionately shifted capital into debt securities of non-stressed euro area countries. Finally, we find that both non-euro area investors' under-investment in stressed countries and stressed euro area investors' over-investment in non-stressed euro area countries ceased after the announcement of the ECB's OMT programme.
Keywords: F34; F36; G15; 330; euro area sovereign debt crisis; foreign investment; gravity model; international capital flows